Hypoxia-Ischemia Induced Age-Dependent Gene Transcription Effects at Two Development Stages in the Neonate Mouse Brain - Dupré, Nicolas; Derambure, Céline; Le Dieu-Lugon, Bérénice; Hauchecorne, Michelle; Detroussel, Yannick; Gonzalez, Bruno J.; Marret, Stéphane; Leroux, Philippe (Frontiers in Molecular Neuroscience, 2020)
Human brain lesions in the perinatal period result in life-long neuro-disabilities impairing sensory-motor, cognitive, and behavior functions for years. Topographical aspects of brain lesions depend on gestational age at the time of insult in preterm or term infants and impaired subsequent steps of brain development and maturation. In mice, the Rice-Vannucci procedure of neonate hypoxia-ischemia (HI) was used at 5 days (P5) or P10, mimicking the development of 30 week-gestation fetus/preterm newborn, or full-term infant, respectively. Transcription response to HI was assessed at 3h, 6h 12h, and 24h after insult, using micro-array technology. Statistical Pathway and Gene Ontology terms enrichments were investigated using DAVID®, Revigo® and Ingenuity Pathway Analysis (IPA®) to identify a core of transcription response to HI, age-specific regulations, and interactions with spontaneous development. Investigations were based on direction, amplitude, and duration of responses, basal expression, and annotation. Five major points deserve attention; i) inductions exceeded repressions (60/40%) at both ages, ii) only 20.3% (393/1938 records) were common to P5 and P10 mice, iii) At P5, HI effects occurred early and decreased 24h after insult whereas they were delayed at P10 and increased 24h after insult, iv) common responses at P5 and P10 involved inflammation, immunity, apoptosis, and angiogenesis. v) age-specific effects occurred with higher statistical significance at P5 than at P10. Transient repression of 12 genes encoding cholesterol biosynthesis enzymes was transiently observed 12h after HI at P5. Synaptogenesis appeared inhibited at P5 while induced at P10, showing reciprocal effects on glutamate receptors. Specific involvement of Il-1 (interleukin-1) implicated in the firing of inflammation was observed at P10. This study pointed out age-differences in HI responses kinetics, e.g. a long-lasting inflammatory response at P10 compared to P5. Whether specific the strong depression of cholesterol biosynthesis genes that could account for white matter-specific vulnerability at P5 or prevent delayed inflammation needs further investigation. Determination of putative involvement of Il-1 and the identification of upstream regulators involved in the delayed inflammation firing at P10 appears promising routes of research in the understandings of age-dependent vulnerabilities in the neonatal brain.